The healing of damage after the plastic deformation of metals - S.V. Smirnov (Fracture and Structural Integrity)
The general regularities of damage healing during the annealing after cold deformation of metal materials are presented in this paper. In categories of damage mechanics the kinetic equations of damage healing during recovery and recrystallization are formulated. Diagrams of damage healing for some metal alloys are presented. The example of use of investigation results for optimization of industrial technology of pipes drawing is presented.